Potensi Isolat Bakteri Proteolitik dari Proses Pembuatan Pupuk Organik sebagai Starter Pengolahan Limbah Peternakan - Nadhira Yahdiyani; Akhmad Hidayatulloh; Lilih Siti Nurhayati (Unpad Press, 2021)
Cattle farms produce waste in the form of feces and urine, the handling of this waste must be managed properly so that it can reduce the adverse effects. One way to use it is to process it into fertilizer. During the process of making microorganism fertilizer helps the process of degradation of complex compounds, one of which plays a role is proteo-lytic bacteria. The purpose of this study is to obtain proteo-lytic bacterial isolates that will be used as a starter in the manufacture of fertilizer. This research was conducted experimentally with research stages including isolation of proteolytic bacteria from the process of making fertilizer, measurement of proteolytic index and morphological cha-racterization of proteolytic bacteria microscopically and microscopically. From the results, 7 isolates of proteolytic bacteria with the largest proteolytic index were 1.51 of NS 3 isolates with the characteristics of small round colonies, flat edges, clear colors, flat surfaces and cell characteristics of bacilli and gram negative isolates.